Innovation and Quality Assessment in Craft Beer Production - Neves, Joana de Sousa (2022)
The yeast Saccharomyces cerevisiae has been used to produce fermented foods and beverages, such as beer, since the earliest civilizations. Nowadays, beer is one of the most popular drinks and the consumption of craft beer, i.e., artisanal beer prepared in small to medium-scale breweries, has in-creased. The constant search for innovative products has inspired brewers and scientists to experiment with new yeasts. In this study, eleven non-beer-brewing S. cerevisiae strains were used to investigate the use of unconventional cultures in beer production. By employing these yeasts in small-scale fer-mentations, we identified strains from wild and domesticated populations that revealed potential for beer production. As the industry grows and more breweries appear, it is relevant to implement good microbial practices for quality control and assessment. Here, we developed protocols to easily and accurately detect diastatic yeasts, a common contaminant in the craft beer industry. Due to the ability to break down complex sugars and consequently to attenuate beer and to produce CO2 inside bottles and cans, diastatic yeasts represent a big threat to brewers, and therefore there is a strong demand for affordable detection methods. In this project, a PCR cycle was optimized to detect the gene responsible for the diastase ability, STA1 and its promoter and a growth-based method with starch was developed. Analyses were performed in samples from a brewery to detect diastatic strains. Moreover, we aimed to study diastatic strains with respect to their ability to grow in beer and produce CO2. We found that when compared to commercial beer and wine-brewing yeasts, the diastatic and beer-brewing yeasts were both able to grow and produce CO2, whereas wine strains grew in beer without producing gas. Finally, we studied the resistance of a diastatic yeast to high temperatures, revealing that these strains are more resistant than beer or wine-brewing yeasts.